2017
DOI: 10.1016/j.ajoc.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral pigmented paravenous retinochoroidal atrophy with retinitis pigmentosa in the contralateral eye: A case report

Abstract: PurposeWe describe a sporadic case of unilateral pigmented paravenous retinochoroidal atrophy (PPRCA) with retinitis pigmentosa (RP) in the contralateral eye.Observationsa 24-year-old female aware of the narrowing of visual field was examined at our hospital. Funduscopic examination revealed left eye showing retinochroidal atrophy along the retinal veins with pigment accumulation while right eye showing peripheral diffuse retinal pigmented epithelium atrophy with bone spicule pigmentation. Fundus autofluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 17 publications
1
7
0
2
Order By: Relevance
“…Recent reports in the literature have described cases of patients with unilateral retinitis pigmentosa and PPRCA in the fellow eye, further supporting the possibility of shared genetic etiologies. 11 Notably, the few reports of hereditary PPRCA in the literature have suggested that inheritance may occur in an autosomal dominant fashion, which may be consistent with the inheritance seen in this family. There may also be male gender predominance.…”
Section: Discussionsupporting
confidence: 80%
“…Recent reports in the literature have described cases of patients with unilateral retinitis pigmentosa and PPRCA in the fellow eye, further supporting the possibility of shared genetic etiologies. 11 Notably, the few reports of hereditary PPRCA in the literature have suggested that inheritance may occur in an autosomal dominant fashion, which may be consistent with the inheritance seen in this family. There may also be male gender predominance.…”
Section: Discussionsupporting
confidence: 80%
“…Few cases of concurrent involvement with PPRCA in one eye and RP in other eye have been reported previously. 10,11 The occurrence of unilateral RP in a mother and bilateral PPRCA in her children has also been reported. 12 Various mutations in Crumbs Homolog 1 (CRB1) gene have been advocated in the pathogenesis of both PPRCA and RP.…”
Section: Discussionmentioning
confidence: 95%
“…Multimodal imaging techniques have led to better characterization of PPRCA [7]. In our case, geographic areas of RPE loss on SD-OCT corresponded to areas of reduced AF and thinning of the outer retinal layers colocalized with the linear increased AF.…”
Section: Discussionmentioning
confidence: 62%